Analysis of Artificial Intelligence Based Science Pedagogy in Internalizing Religious Moderation Values in the Era of Disruption - Tb. M. Adrie Admira; Fadhil Nur Hidayat (Khazanah: Journal of Islamic Education and Science, 2026)
This study was motivated by the increasing complexity of educational challenges in the era of disruption, particularly in integrating artificial intelligence with the need to internalize religious moderation values. The gap between the use of technology in science learning and the strengthening of value dimensions became the primary concern addressed in this study. This research aimed to analyze the characteristics of artificial intelligence-based science pedagogy and its role in internalizing religious moderation values. The study employed a descriptive qualitative approach using a meta-analysis method of scientific literature published between 2016 and 2025 from reputable digital databases. Data were collected through systematic documentation with standardized selection protocols, while data analysis was conducted using thematic analysis to synthesize findings across studies. The results indicated that artificial intelligence-based science pedagogy demonstrated adaptive, interactive, and reflective characteristics that were effective in fostering critical awareness, tolerance, and inclusive attitudes among learners. The integration of religious moderation values was most optimally achieved through technology-based reflective dialogue approaches. This study contributed theoretically by proposing an integrative framework combining science pedagogy, artificial intelligence, and value - based education, as well as offering practical implications for developing contextual and character-oriented learning in the era of disruption.